Advanced oxidation processes for elimination of xylene from waste gases - Prostejovský, Tomás (2020)
The elimination of xylene was experimentally studied using advanced oxidation process in a two-step pilot plant photochemical unit with the use of UV irradiation combined with ozone (first step) and with hydrogen peroxide solution (second step). The influence of the initial xylene concentration and air flow rate was investigated. A mathematical model of the first step of the unit applying UV/O3 treatment was developed. Xylene conversion decreased with increasing its initial concentration and increasing flow rate of the air (lowering residence time in the unit). The highest xylene conversion (95 %) was achieved with the initial concentration 50 ppmv and the flow rate 57 m3· h−1. Based on the model results for the first photolytic step of the pilot plant unit, the main pathway of the elimination of xylene is its reaction with hydroxyl radicals which are formed both by the reaction of ozone with water/humidity but also by the reaction of singlet oxygen (formed by the decomposition of ozone) with water/humidity. Calculated figures-of-merit showed that the pilot plant unit is more energy-cost-efficient for the higher flow rates of the waste gas. The technology using advanced oxidation processes seems promising for the elimination of organic compounds from the air, although further studies are necessary.